Implementation Of Hypertension Management Program In The Work Area Of The Ri Sidomulyo Puskesmas Pekanbaru City 2022: Implementasi Program Pengelolaan Hipertensi Diwilayah Kerja Puskesmas Ri Sidomulyo Kota Pekanbaru Tahun 2022 - Yuli Wulandari; Jasrida Yunita; Welly Sando; Ahmad Hanafi; Zainal Abidin (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Hypertension is an increase in systolic blood pressure 140 mmHg and diastolic blood pressure ≧90 mmHg. In addition, in primary medical practice hypertension is one of the most common diseases found. The National Heart, Lung, and Blood Institute (NHLBI) believes that one in three patients has hypertension. This study aims to find out how the implementation of the hypertension management program in the working area of the RI Sidomulyo Public Health Center in 2022. This research was conducted using a qualitative descriptive research design with in-depth interviews, observation and document tracking methods, to 5 informants consisting of the Head of the Public Health Center, the Person in Charge of the PTM Program , Head of Administration, Doctors, and Nurses. This research was carried out in Mei 2022 at the Indonesian Health Center Sidomulyo Pekanbaru City. The results of this study indicate that human resources are adequate but the coordination and cross-programme are not running well. Facilities and infrastructure are still inadequate, such as the unavailability of a technical guidebook for the discovery and management of hypertension and no instructions for implementing the hypertension program. covid-19, in addition to the puskesmas itself, the visit, judging from the achievements, the SPM is not too good, because many people are lazy to seek treatment and do not care about their health and the implementation of the PTM Posbindu in the Implementation of the Hypertension Management Program in the Work Area of the Indonesian Health Center Sidomulyo was known before the pandemic Covid-19 activities at the Posbindu implementation have been going well, but during the pandemic the activities did not run and were not optimal, apart from the lack of Posbindu.